Quantifying and understanding the triboelectric series of inorganic non-metallic materials - Haiyang Zou (Nature Portfolio, 2020)
The mechanism of contact electrification remains a topic of debate. Here, the authors present a quantitative database of the triboelectric charge density and band structure of many inorganic materials, verifying that contact electrification between solids is an electron quantum transition effect.